R&D cooperation and innovation activities of firms: Evidence for the German manufacturing industry - Wolfgang Becker; Jürgen Dietz (Universität Augsburg, Institut für Volkswirtschaftslehre, 2002)
The aim of the paper is to investigate in a simultaneous equation framework the role of R&D cooperation in the innovation process under two specific aspects. First, the analysis is concentrated on the impact of R&D cooperation - in line with other factors - on firm's innovation input and output. Second, it will be analyzed how the number of cooperation partners affects the development of new products. Starting with the discussion of theoretically expected effects of successfully R&D cooperation on the innovation activities of firms, the importance of inter-organizational arrangements in R&D is empirically investigated for firms in the German manufacturing industry. The estimation results can be summarized as follows: In the German manufacturing industry, R&D cooperations are used complementary in the innovation process, enhancing the innovation input and output of firms measured by the intensity of inhouse R&D respectively the realization of product innovations. On the input side, the intensity of inhouse R&D also stimulates the probability and the number of R&D cooperations with other firms and institutions.
urn:nbn:de:bvb:384-opus4-712382
Keywords: O31; L10; I20; L60; 330; R&D cooperation; innovation behaviour; technological opportunities; manufacturing industry